The investigation of Cut-and-cover, top-down construction method for a metro underground station; case study: 'Naghsh-e-Jahan Metro Station, Esfahan, Iran' - Cambyse BEHNIA; Amir TAVALLAIE NEJAD; Hossein SALARI RAD (Journal of Materials and Engineering Structures, 2022)
Naghsh-e-Jahan subway station is located in Esfahan historical context with 186 meters' distance to the Sheikh Fazlolah mosque – one of the historical cosmopolitan attractions. The subway station is in a shallow depth, soft surrounding soils and with wide span and in a downtown location, have made the situation so critical that precise assessments, not only for the station support but also for compensating the ground settlement, are needed. One of the prerequisite procedures for large underground structures, the cut-and-cover approach, is constructed top-down using the Diaphragm Wall system. This method can be functional in conditions where minimum vertical displacements are essential since roof covering and improvement can be performed even when the excavation operation is not terminated. The embankment process can be done just right after the roof slab is complete and reaches reliable strength. This study uses the Finite Element method to simulate all the construction stages and analyze the ground behavior. It has been observed that the width and the length of diaphragm walls and middle barrettes on the ground settlements. Ground settlement for various stages of excavation at the cross-section and longitudinal section of the station is shown that settlements are spandrel and maximum settlements occur close to the diaphragm walls. As excavation continues, ground surface settlements become concave, and the maximum surface settlements occur at a bit of distance from the diaphragm walls for about 17mm. Furthermore, the diaphragm wall's thickness of 100 cm of diaphragm wall is recommended for optimum values.